Technological properties and fire performance of medium density fibreboard (MDF) treated with selected polyphosphate-based fire retardants. Issue 5 (2nd September 2020) - Mantanis, George I.; Martinka, Jozef; Lykidis, Charalampos; Ševčík, Libor
ABSTRACT: The objective of the work was to evaluate the efficacy of two new polyphosphate-based fire retardants (FRs) and one commercial product named Siriono ® on the fire performance and physical–mechanical properties of medium density fibreboard (MDF) fabricated in the laboratory from Scots pine ( Pinus sylvestris L.) wood. The fibres were treated with aqueous solutions of fire retardants, at 12% loading (dry salt on dry wood), and bonded with a melamine urea formaldehyde (MUF) adhesive. The physical and mechanical properties of panels were assessed using the European standards, whereas their fire performance was evaluated using an in-house method and the Cone calorimeter. In overall, the chemicals added enhanced the fire and smoke properties of the panels to varying degrees. Critical FR parameters such as peak heat release rate (peak HRR), total heat release (THR) and total smoke production (TSP) were significantly improved in the FR-treated panels, as exhibited in cone calorimeter tests. However, the internal bond strength of treated panels largely decreased by the addition of fire retardants, while thickness swell and water absorption negatively affected to a significant extent. In contrast, the formaldehyde release of the panels was considerably decreased at the E1 class level, with the incorporation of the polyphosphate-based additives.